2023
DOI: 10.1590/1519-6984.273525
|View full text |Cite
|
Sign up to set email alerts
|

Fish diversity in the rivers that drain the Baixada Maranhense and the Mearim basin in northeastern Brazil

D. Limeira-Filho,
P. S. S. Moraes,
M. S. Almeida
et al.

Abstract: The Baixada Maranhense Environmental Protection Area of the Brazilian state of Maranhão encompasses a biologically rich region that includes the basins of four principal rivers, the Mearim, Pericumã, Pindaré, and Turiaçu, which form a complex of wetlands. The present study provides a comprehensive inventory of the fish fauna of the rivers that drain the Baixada Maranhense based on the identification of voucher specimens that were deposited in a scientific collection. Expeditions were conducted between 2014 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, a greater sampling effort and a more detailed study would be necessary to better understand this scenario. Some cases of species being introduced into the hydrographic basins of Maranhão have been reported [ 24 , 89 , 91 ]. In the present study, four specimens were collected from the Preto River, in the municipality of São Benedito do Rio Preto, in the state of Maranhão, which corresponds to one of the localities sampled by Vieira et al [ 91 ], in the most comprehensive survey ever conducted of the basin of the Munim River.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a greater sampling effort and a more detailed study would be necessary to better understand this scenario. Some cases of species being introduced into the hydrographic basins of Maranhão have been reported [ 24 , 89 , 91 ]. In the present study, four specimens were collected from the Preto River, in the municipality of São Benedito do Rio Preto, in the state of Maranhão, which corresponds to one of the localities sampled by Vieira et al [ 91 ], in the most comprehensive survey ever conducted of the basin of the Munim River.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Pimelodus , based on the use of molecular markers, confirmed the existence of two independent evolutionary lineages from the trans-Andean region, which were described as new species [ 23 ]. Studies of this type are still limited in the Brazilian Northeast, however, and most of the Pimelodus taxa known to occur in the hydrographic basins of the state of Maranhão have been catalogued based solely on classical taxonomic criteria [ 24 ]. In addition, given the confused taxonomy of the genus, the nomen P. blochii , for example, has been attributed arbitrarily to many types of long-whiskered catfish from different localities in the Amazon basin, which likely represent more than one species [ 25 ].…”
Section: Introductionmentioning
confidence: 99%